Glycerol contributes to tuberculosis susceptibility in male mice with type 2 diabetes - Martinez, Nuria (2023)
Diabetes mellitus increases risk for tuberculosis disease and adverse outcomes. Most people with both conditions have type 2 diabetes, but it is unknown if type 1 and type 2 diabetes have identical effects on tuberculosis susceptibility. Here we show that male mice receiving a high-fat diet and streptozotocin to model type 2 diabetes, have higher mortality, more lung pathology, and higher bacterial burden following Mycobacterium tuberculosis infection compared to mice treated with streptozotocin or high-fat diet alone. Type 2 diabetes model mice have elevated plasma glycerol, which is a preferred carbon source for M. tuberculosis. Infection studies with glycerol kinase mutant M. tuberculosis reveal that glycerol utilization contributes to the susceptibility of the type 2 diabetes mice. Hyperglycemia impairs protective immunity against M. tuberculosis in both forms of diabetes, but our data show that elevated glycerol contributes to an additional adverse effect uniquely relevant to type 2 diabetes.